theorem zsndznsub (m n: nat): $ zsnd (m -ZN n) = n - m $;
Step | Hyp | Ref | Expression |
1 |
|
|
zfst (-uZ (m -ZN n)) = zsnd (m -ZN n) -> zfst (-uZ (m -ZN n)) = n - m -> zsnd (m -ZN n) = n - m |
2 |
|
|
zfst (-uZ (m -ZN n)) = zsnd (m -ZN n) |
3 |
|
|
zfst (-uZ (m -ZN n)) = n - m -> zsnd (m -ZN n) = n - m |
4 |
|
|
zfst (-uZ (m -ZN n)) = zfst (n -ZN m) -> zfst (n -ZN m) = n - m -> zfst (-uZ (m -ZN n)) = n - m |
5 |
|
|
-uZ (m -ZN n) = n -ZN m -> zfst (-uZ (m -ZN n)) = zfst (n -ZN m) |
6 |
|
|
|
7 |
|
|
zfst (-uZ (m -ZN n)) = zfst (n -ZN m) |
8 |
|
|
zfst (n -ZN m) = n - m -> zfst (-uZ (m -ZN n)) = n - m |
9 |
|
|
|
10 |
|
|
zfst (-uZ (m -ZN n)) = n - m |
11 |
|
|
|
Axiom use
axs_prop_calc (+5)
(ax_1,
ax_2,
ax_3,
ax_mp,
itru),
axs_pred_calc (+8)
(ax_gen,
ax_4,
ax_5,
ax_6,
ax_7,
ax_10,
ax_11,
ax_12),
axs_set (+2)
(elab,
ax_8),
axs_the (+2)
(theid,
the0),
axs_peano (+9)
(peano1,
peano2,
peano5,
addeq,
muleq,
add0,
addS,
mul0,
mulS)